Mechanical Performance of Two Different Gradations of Porous Asphalt Mixtures Incorporating Bamboo Fiber - Md Shahnewaz, Shoaib; Khairil Azman, Masri; Nadiatul Adilah, Ahmad Abdul Ghani; Putra Jaya, Ramadhansyah; Chin, Siew Choo (Suranaree University of Technology, 2024)
Porous asphalt (PA) is used to control the effects of storm water and reduce runoff. However, due to high air void content, it decreases the volumetric properties and tensile strength of PA. Thus, this study aims to investigate the inclusion of bamboo fiber enhances the volumetric properties of PA and contributes to the resolution of the low tensile strength problem. Stability, flow, density, and stiffness are some variables considered. Other considerations include the use of a void filled with bitumen (VFB) with two separate gradations of polyacrylonitrile (PA) and four different percentages of bamboo fiber (0.2 percent, 0.3 percent, 0.4 percent, and 0.5 percent). In addition, the permeability, binder drain-down, and Cantabro loss tests are used to analyze the modified PA's physical qualities. According to the findings, including bamboo could contribute considerably to improving the inner structure of PA for both grades. Besides, additional bamboo fiber significantly reduces the abrasion value by 80%, whereas the binder drain down improved the volumetric properties and preserved the permeability characteristics of PA. Therefore, it can be concluded that the existence of bamboo PA can significantly improved the mechanical performance of PA.